(untitled) (AYUSHDHARA, 2025)
The ancient science of Ayurveda had a great emphasis on Sneha kalpana which is a pharmaceutical process of preparing oleaginous medicaments like medicated oils and ghee to extract and enhance the therapeutic properties of herbs used both internally and externally. Application of these medicinal oils will help in the nourishment of the Dhatus (tissues), improves the digestion, and enhance the body’s natural healing processes. Vishadanam taila is one such formulation which is mentioned in the Gadanigraha, Tailadhikara highlighting the method of preparation through the traditional procedure Bhanupaka for the management of Vicharchika. Bhanupaka is a unique form of preparing the medicine under the intense heat of sun rays by enhancing the therapeutic efficacy and preserving the volatile principles of the ingredients. Kampillaka, Haridra, Daruharidra, Shala niryasa, Guggulu, Chitraka, Vidanga, Vatsanabha and Katu taila are the ingredients. The pharmaceutical procedures involved in this process are Shodhana, Kalka nirmana and preparation of Taila. Total 768ml of Taila was prepared with a loss of 18ml in the total product. The present study has been planned to standardize the method of preparation of Vishadanam Taila according to the method explained in the classical texts.